NEUROBIOLOGY OF THE IMPACT OF AVERSIVE EXPERIENCES ON LEARNING: A SCOPING REVIEW - Defante, Maria Luiza Rodrigues; Monteiro, Sarah Oliveira Nunes; Teixeira, Lucas Martins (Brazilian Medical Students, 2024)
Introduction: The memory processes sustain the activity of learning, which requires attention and directed focus. Classroom aversive experiences such as anxiety disorders, chronic stress and fear can modulate the learning processes. The mechanism consists in a reorientation, mediated by neurohumoral mechanisms, involving the hippocampus and the amygdala, prejudicing the acquisition of knowledge. Method: This study is a scoping review in which the online databases PubMed and LILACS were used to identify papers using an unified search strategy. 18 papers published between 2017 and 2022 composed the scoping review. Result: The selected studies met the eligibility criteria of online availability, traumatic experiences and learning association and correlation between frightening and stressful experiences with memory consolidation. As an acute consequence of stress, high amounts of norepinephrine and cortisol, a glucocorticoid, are released in the body. The interaction between these two agents, especially in the central nervous system, impairs working memory functioning and interrupts the attention functions of the prefrontal cortex, while directing attention only to threatening stimuli, making it hard to non-threatening information consolidation. Chronically, the adverse component is mediated mostly by cortisol, impairing learning through basically two mechanisms. One of them is by disturbing hippocampal functioning and amygdala signaling, leading to long-term memory deficits and facilitating the persistence of fear memories. The other is through avoidance behavior, which works as a defense against unfavorable stimuli, leading the individual to create an obstacle to new learning. Conclusion: In situations of stress, anxiety and fear, there are mechanisms in the hippocampus and amygdala mediated by neurotransmitters and hormones that can impair memory consolidation and prejudice learning.